PENGARUH PENERAPAN TEKNIK COPY THE MASTER (CTM) TERHADAP KETERAMPILAN MENULIS TEKS DESKRPSI SISWA KELAS VII SMP NEGERI 12 PADANG - Nusantara, Melati; Arief, Ermawati; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACT This article is written to determine the research aimed to analyze the students skill of writing description text in VII (seventh) grade of SMP Negeri 12 Padang before and after implementation of the CTM technique and to analyze the effect CTM technique toward the skill of writing description text in VII (seventh) grade of SMP Negeri 12 Padang. The data of this research are the test score of writing description text skill before and using CTM technique of the students in class VII SMP Negeri 12 Padang. The data was being analyzed with the percentage formula, the arithmetic mean formula and the t-test. The instrument of the research is performance test, that is test to write description text before and after using CTM technique. There are two findings of this research. First, the skill of students in the VII (seventh) grade of SMP Negeri 12 Padang of writing description text before using the CTM technique with qualification C (Cukup) with average 58,5. Second, the skill of students in the VII (seventh) grade SMP Negeri 12 Padang of writing description text after using the CTM technique with qualification B (Baik) with average 82,19. Third, according to the t-test, alternative hypothesis (H1) was accepted in the significance percentage 95% and the degrees of freedom (df) = n-1 because of the taritmatic> ttable, which is 10,71 > 1,70.Kata kunci: Pengaruh, copy the master, menulis teks deskripsi